Unveiling Koreanness in Yoon Ha Lee's Dragon Pearl - Kang, Byoung Yoong (Acta linguistica asiatica, 2025)
The paper explores the representation of Koreanness in Yoon Ha Lee’s Dragon Pearl, a novel that uniquely blends elements of Korean culture with the space opera genre. By examining key cultural markers such as character names, traditional food, and folklore (notably the gumiho), this study highlights how the novel portrays a diasporic sense of identity and belonging. Furthermore, the paper delves into the challenges and strategies of translating these cultural elements into Korean. Through case studies of key passages, it discusses how to maintain cultural nuance and the author’s intent while adapting the work for a Korean readership. Ultimately, this paper underscores the importance of preserving cultural integrity translating science fiction works that embody cross-cultural narratives.
Keywords: ameriška književnost; diaspora; korejska kultura; korejska mitologija; korejskost; prevajalske strategije; vesoljske opere